Organic nitrogen utilisation by an arbuscular mycorrhizal fungus is mediated by specific soil bacteria and a protist - Rozmoš, Martin; Bukovská, Petra; Hršelová, Hana; Kotianová, Michala; Dudáš, Martin; Gančarčíková, Kateřina; Jansa, Jan (The ISME journal, 2022)
Arbuscular mycorrhizal (AM) fungi lack efficient exoenzymes to access organic nutrients directly. Nevertheless, the fungi often obtain and further channel to their host plants a significant share of nitrogen (N) and/or phosphorus from such resources, presumably via cooperation with other soil microorganisms. Because it is challenging to disentangle individual microbial players and processes in complex soil, we took a synthetic approach here to study 15N-labelled chitin (an organic N source) recycling via microbial loop in AM fungal hyphosphere. To this end, we employed a compartmented in vitro cultivation system and monoxenic culture of Rhizophagus irregularis associated with Cichorium intybus roots, various soil bacteria, and the protist Polysphondylium pallidum. We showed that upon presence of Paenibacillus sp. in its hyphosphere, the AM fungus (and associated plant roots) obtained several-fold larger quantities of N from the chitin than it did with any other bacteria, whether chitinolytic or not. Moreover, we demonstrated that adding P. pallidum to the hyphosphere with Paenibacillus sp. further increased by at least 65% the gain of N from the chitin by the AM fungus compared to the hyphosphere without protists. We thus directly demonstrate microbial interplay possibly involved in efficient organic N utilisation by AM fungal hyphae.
Keywords: dusík; Mycorrhizae; kořeny rostlin; Plant Roots; Bacteria; půda; mykorhiza; fosfor; Phosphorus; Nitrogen; Soil